Miners' wages. Conciliation board : minutes of proceedings at a joint conference between representatives of the Federated Coal Owners and the Miners Federation of Great Britain at the St Martin's Town Hall, Tuesday, 3rd April, 1894. fourth meeting of the board. Lord Shand in the chair - Miners' Federation of Great Britain
Mention de couv. : "Private" [document interne]- transcript of the shorthand notes of Messrs. J. Moore & son